Analisis Pengaruh Firm Size, Firm Age, Leverage, Dan Growth Terhadap Kinerja Perusahaan - Megawati, Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this research is to analyze the effect of firm size, firm age, leverage, and growth on firm performance in manufacturing companies listed in Indonesia Stock Exchange period 2015 – 2017. This research examines 162 samples using purposive sampling method. The result of this research shows that firm size and leverage have significant effect on firm performance, while firm age and growth have no significant effect on firm performance